Epidemiology and secular trends of malignant lymphoma in Japan: Analysis of 9426 cases according to the World Health Organization classification. (11th October 2018) - Muto, Reiji; Miyoshi, Hiroaki; Sato, Kensaku; Furuta, Takuya; Muta, Hiroko; Kawamoto, Keisuke; Yanagida, Eriko; Yamada, Kyohei; Ohshima, Koichi
Abstract: This study provides an overview of the epidemiology and secular trends of malignant lymphoma in Japan. Using data from clinics and hospitals throughout Japan, we analyzed 9426 cases of malignant lymphoma diagnosed in 2007‐2014. We show that the proportion of follicular lymphoma and methotrexate‐associated lymphoproliferative disorder increased during this time, as did the onset age for follicular lymphoma and diffuse large B‐cell lymphoma. Significant increases in onset age for follicular lymphoma and diffuse large B‐cell lymphoma were observed in both men and women (all P values <0.0001 except for P  = 0.0448 for the latter disease in women). Further studies are required to determine the reasons for the higher proportion of and onset age for these lymphomas. Additionally, we believe that continued observation of these trends is necessary. Abstract : The age at onset of follicular lymphoma has been aging during the period 2007‐2014. A similar tendency was also observed in DLBCL.